(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Stuchalo A. A. The role of the Ukrainian language by professional direction in the formation of a future veterinarian. The article characterizes the position of the Ukrainian language in the formation of the future specialist. The attempt of pedagogical conditions analysis of professional communication formation of agrarian university students on the basis of the Ukrainian language for the professional orientation has been made.